Nurturing volunteerism spirit among students by blood donation programme - Muhamad Faris Hamidin; Mohd Faisal Hushim; Suhairi Ismail; Md Norrizam Mohmad Ja'at @ Mohd Noh; Mohd Nazrin Musling; Zolhafizi Jaidi; Chia Sze Yee; Mohamad Khairi Aliashak (Penerbit Universiti Kebangsaan Malaysia, 2024)
Health-related technologies are rapidly evolving, with significant contributions from government and industry stakeholders. Healthcare technology is defined as any technology, including medical devices, IT systems, algorithms, artificial intelligence (AI), cloud and blockchain, designed to support healthcare organisations. Despite these advancements, one critical element the human blood cannot be artificially created in laboratories. Blood is vital for life and is required for transfusions to support accident victims, surgical and cancer patients, women with complications during pregnancy and childbirth, children with severe anaemia, malaria patients, and malnourished individuals. In Malaysia, the healthcare sector needs approximately 15,000 to 17,000 bags of blood per month, underscoring the importance of maintaining adequate blood reserves. This article aims to share some initiatives and significant actions that have been taken by the Student Leadership Council (SLC-KKKP) to conduct regular blood donation campaigns and programmes. This programme is conducted monthly; at least 50 bags are collected each time. The success of these initiatives relies heavily on the spirit of student volunteerism. Awareness and supportive campaigns are actively being done to promote the importance of this programme. After two years of continuous and never-ending commitment, the student residential college (Kolej Kediaman Kampus Pagoh – KKKP) has been recognised and awarded as The Most Committed Organisation for Blood Donation Programme by the Ministry of Health Malaysia (MOH) for two consecutive years, and The Highest Collected Blood Organisation for the year of 2022.